KAIN TENUN IKAT SEBAGAI WISATA BUDAYA KABUPATEN SIKKA - Octaviani, Lenny Kurnia; Komalasari, Sri Andini (Kepariwisataan: Jurnal Ilmiah, 2020)
The diversity of Sikka culture is reflected in the art of weaving that is a symbol of the great tribal and indigenous people of Sikka that need to be lifted to the surface and be preserved. The method that the authors use in this research is a qualitative methode. The diversity of woven fabricin the Sikka district has a different meaning and meaning not only to art, but it has also considered a social, religious, cultural,and economic symbol. With the growth of many young generation which have begun to ignore the culture woven into the fabric. The need for cooperation between government, weavers, and community inside preserve of weaving culture and preserving culture heritage is not lost in the ingestion of the era. Keywords: Ikat Sikka Weaving, Tourism Culture, SWOT Analysis